Nitrogênio com ou sem calcário superficial para recuperação do capim-marandu - Balieiro Neto, Geraldo [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
A degradação de cerca de 60 milhões de hectares de pastagens no Brasil afeta diretamente o estado nutricional dos rebanhos, conduzindo os pecuaristas a abrirem novas áreas de floresta, resultando em grave impacto de ordem econômica e ambienta!. A recuperação direta por meio da reposição dos nutrientes extraídos do solo ao longo dos anos representa menor risco ao produtor e reais possibilidades de adoção pela maior parte dos pecuaristas. Com este trabalho, objetivou-se avaliar os efeitos de nitrogênio (O, 100, 200, 300 e 400 kg/halano) com ou sem aplicação superficial de calcário nos atributos químicos de um Latossolo Vermelho distroférrico, nutrição mineral da planta, composição química, digestibilidade in vitro da matéria seca (DIVMS), características estruturais e massa de forragem de capim-Marandu. Foi utilizado um delineamento em blocos ao acaso em arranjo fatorial 2 X 5 com quatro repetições no esquema de parcela subdividida com medidas repetidas no tempo. A aplicação de calcário aumentou o pH e reduziu a acidez potencial nas camadas de O a 5 e 5 a 10 cm, 20 meses após aplicação, aumentou os teores de Ca e Mg, incrementou SB e a CTC na camada de O a 5 cm e saturação por bases nas camadas de O a 5 e 5 a 10 cm. O nitrogênio provocou acidificação do solo nos tratamentos sem calcário. O calcário aumentou a concentração de Ca nas lâminas foliares 11 meses após sua aplicação...

The degradation of 60 million hectares of pastures in Brazil directly affects the nutritional status os cattle herds drives farmers the open new forest areas resulting in great economic and environmental impact. The recovery through the replacement of nutrients extracted from the soil along the years represents lower risk to farmers and real possibilities of adoption by the majority of farmers. It was aimed at to evaluate the effects of nitrogen doses (O, 100, 200, 300 and 400 kg/ha of N by year) with or without surface liming on the chemical attributes of a red Latosol (Oxisol), plant mineral nutrition, chemical composition, in vitro digestibility, structural characteristic and herbage mass of Marandu-grass. The analysis of variance was performed based on a complete randomized block at factorial arrangement 2 X 5 with four replications design in a split-split-plot scheme with repeated measures over time. The lime increased the pH and reduced the acidity potential in the layers from O to 5 and 5 to 10 cm, increased the content of Ca, Mg, base sum and cation exchange capacity in the layer from O to 5 cm and base saturation in the layers from O to 5 and 5 to 10 cm. There was positive linear effect of N on the content of K in the layer from O to 5 cm of the soil and negative linear effect on the content of S in the soil layers from 10 to 20 and 20 to 30 cm of depth. There was positive linear effect of dose of N on the content of Ca, P, Mg and S during the summer months and negative linear effect on the same characteristics during the winter months. The content of N and K increased linearly to the increase of the doses of N in ali of months. In the months January and August there was quadratic effect of N doses on the leaf N content... (Complete abstract, click electronic access below)
Keywords: The soil fertility; Marandu grass; Structural characteristic; Mineral nutrition; nutritional value; Urea; Solos - Fertilidade; Calcário; Uréia; Características estruturais; Nutrição mineral; Capim marandu; Valor nutritivo